Direct Determination of Required Rigidities for Multiple-Bracing Frames - Wechsler, Marius B. (Engineering Journal, 1984)
The analysis of vertical braces of a braced steel structure requires concurrent consideration of drift and strength requirements. Done by hand calculations, or even by digital computers, this kind of analysis is time-consuming and expensive. The method presented in this paper avoids this tedious work, even though only the simplest arithmetic calculations are used. The simplicity of the described algorithm permits implementation on a pocket calculator, which makes it an important aid for the design of braced steel structures. The guidelines presented here allow the direct determination of the required rigidities for both directions of a braced steel structure so that overloading of braces can be prevented.